Pengaruh Penambahan Fermentasi Daun Murbei (Morus spp.) Dalam Formulasi Pakan untuk Menstimulasi Molting Kepiting Bakau (Scylla serrata) - Sulfah Salnida Dewi; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Journal of Aquaculture Science, 2023)
One of the factors in aquaculture activities that affect the production and growth process of mud crab is molting. Several techniques have been developed to accelerate the molting of mud crabs, namely ablation, mutilation, and supplementation. One form of supplementation is through the use of fermented mulberry leaves in mud crab feed. Therefore, this study aimed to analyze the effect of adding fermented mulberry leaves (Morus spp.) in feed to stimulate the molting of mud crabs (S. serrata). This research was carried out in traditional ponds in Bugis Village, Sape District, Bima Regency, for 60 days. The method used was an experimental method with a completely randomized design (CRD) consisting of five treatments and three replications, namely control treatment/trash fish (P1), 20% Mulberry Leaf Fermentation (P2), 25% (P3), 30% (P4), and 40% (P5). Research parameters comprise frequency and percentage of molting, absolute growth, specific growth rate, feed utilization efficiency, feed conversion ratio, survival rate, and water quality. The results showed that the combination test feed of fermented mulberry leaf (Morus spp.) in the mud crab (S. serrata) diet did not affect all the parameters measured. The provision of mangrove crab feed formulation with a concentration of 25% mulberry leaf fermentation (P3) and control treatment (P1) gave a faster initial molting, which was the first 10 days of the rearing period with the highest average frequency and percentage of molting of 37 and 41%, respectively.